The determinants of Foreign Direct Investment (FDI) in Malaysia / Norsyamimi Zakwan - Zakwan, Norsyamimi (2015)
As Malaysian economy continued record repaid progress on the back of sustained economic growth, the contribution of Foreign Direct Investment (FDI) to the Malaysia economic expended at a faster pace since early 1970’s. Thus, the major concern on this study is to discuss the Determinants of Foreign Direct Investment in Malaysia over the period 1983 to 2012. In this paper, regression analysis will be carried out. The result shows factors like market size and inflation rate are significant with foreign direct investment in Malaysia.